Risk of irregular menstrual cycles and low peak bone mass during early adulthood associated with age at menarche - Anai, Takanobu; Miyazaki, Fumiko; Tomiyasu, Toshiko; Matsuo, Toshiko (Pediatrics international, 2001)
Background : The risk of irregular menstrual cycles and low peak bone mass of the lumbar spine in young adult women, associated with age at menarche, has not been clearly defined. The aim of this study was to investigate this further. Methods : A total of 180 college females aged 20–23 years were surveyed about menstruation, exercise, and calcium intake by means of a questionnaire. We also measured vertebral bone mineral density in these women by dual energy X‐ray absorptiometry. The subjects were divided into six groups according to their age at menarche. Comparisons were made of the mean body mass index (BMI) and T‐scores (the ratio to the mean bone mineral density of young adult Japanese women) among those groups, and odds ratios of irregular menstrual cycles and low peak bone mass less than 87% (– 1 standard deviation (SD) of T‐scores were calculated using the mean menarcheal age (12 years) group as a control. Results : The mean BMI and T‐scores were significantly lower in delayed menarche groups (equal to or more than 13 years) compared with early menarche groups (equal to or less than 12 years). The odds ratios of irregular menstrual cycles were 5.9 (95% confidence intervals (CI) 1.7–20.6), 13.7 (95% CI 3.6–51.6), and 73 (95% CI 6.5–813.9) in the 13‐, 14‐, and more than 14 years menarcheal age groups, respectively. The odds ratio of low peak bone mass less than 87% (– 1SD) was 3.4 (95% CI 1.1–10.3) in the 14 years menarcheal age group. Conclusions : Young adult women with delayed menarche may be at high risk for irregular menstrual cycles and low peak bone mass.